RAGE binds preamyloid IAPP intermediates and mediates pancreatic β cell proteotoxicity - Abedini, Andisheh (J Clin Invest, 2018)
Islet amyloidosis is characterized by the aberrant accumulation of islet amyloid polypeptide (IAPP) in pancreatic islets, resulting in β cell toxicity, which exacerbates type 2 diabetes and islet transplant failure. It is not fully clear how IAPP induces cellular stress or how IAPP-induced toxicity can be prevented or treated. We recently defined the properties of toxic IAPP species. Here, we have identified a receptor-mediated mechanism of islet amyloidosis–induced proteotoxicity. In human diabetic pancreas and in cellular and mouse models of islet amyloidosis, increased expression of the receptor for advanced glycation endproducts (RAGE) correlated with human IAPP–induced (h-IAPP–induced) β cell and islet inflammation, toxicity, and apoptosis. RAGE selectively bound toxic intermediates, but not nontoxic forms of h-IAPP, including amyloid fibrils. The isolated extracellular ligand–binding domains of soluble RAGE (sRAGE) blocked both h-IAPP toxicity and amyloid formation. Inhibition of the interaction between h-IAPP and RAGE by sRAGE, RAGE-blocking antibodies, or genetic RAGE deletion protected pancreatic islets, β cells, and smooth muscle cells from h-IAPP–induced inflammation and metabolic dysfunction. sRAGE-treated h-IAPP Tg mice were protected from amyloid deposition, loss of β cell area, β cell inflammation, stress, apoptosis, and glucose intolerance. These findings establish RAGE as a mediator of IAPP-induced toxicity and suggest that targeting the IAPP/RAGE axis is a potential strategy to mitigate this source of β cell dysfunction in metabolic disease.